Bazy danych o organizacjach pozarządowych - Iwankiewicz-Rak, Barbara (Data Bases about Non-Governmental Organizations, 2006)
The paper, published in Poland, presents the main sources of information concerning non-govemmental organizations which have the character of registers and data bases being worked out on the base of the results of quality research of NGOs sector. On account of their substantive range and reliability the presented sets of information can be used in marketing research carried out by business companies and non-profit organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 568-574